Glass composition, inorganic glass powder, preparation method of inorganic glass powder, automobile pressed glass conductive silver paste and preparation method of automobile pressed glass conductive silver paste

By adopting a silver powder system with a polycrystalline-gap structure and a low melting point glass powder, combined with the mixing of special functional additives and organic carriers, a kind of automotive pressed glass conductive silver paste was prepared, which solved the problem that the existing technology could not meet the pressing process requirements, and achieved excellent acid and alkali resistance, welding, wear resistance and ink matching.

CN119898957APending Publication Date: 2025-04-29SHANGHAI BAOYIN ELECTRONICS MATERIALS CO LTD

Patent Information

Application Number
CN202411978852.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing conductive silver paste cannot meet the technical requirements of the pressing process, including the shortcomings of low sintering process window, acid and alkali resistance, welding performance, wear resistance and ink matching.

Method used

Using a silver powder system with a polycrystalline-gap structure, a low-melting glass powder and various special functional additives, a kind of automotive pressed glass conductive silver paste is prepared by mixing it with an organic carrier and slurrying it. The silver paste has excellent acid and alkali resistance, welding performance, wear resistance and ink matching when the sintering process window is low.

Benefits of technology

In the pressing process, the efficient sintering of conductive silver paste, excellent acid and alkali resistance, good welding strength, significant wear resistance and good ink matching are achieved, and the technical requirements of the pressing process are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898957A_ABST
    Figure CN119898957A_ABST
Patent Text Reader

Abstract

The invention relates to a glass composition, inorganic glass powder and a preparation method thereof, and automobile pressed glass conductive silver paste and a preparation method thereof. The glass composition comprises a first glass composition and a second glass composition, wherein the first glass composition and the second glass composition respectively comprise Bi2O3, SiO2, B2O3, Sb2O3, Na2O, Al2O3, K2O, Li2O and CaO; the glass is prepared from the following raw materials: Bi2O3, B2O3, ZnO, SiO2, CaF2, Al2O3, MgO and Sb2O3. The preparation method of the inorganic glass powder comprises the following steps: mixing two glass compositions, heating, melting, quenching with water, and ball-milling into powder. The preparation method of the conductive silver paste for the automobile pressed glass comprises the following steps: mixing the organic carrier, the inorganic glass powder, the functional additive and the spherical silver powder, and grinding to obtain the conductive silver paste for the automobile pressed glass. Compared with the prior art, the silver paste has the advantages of being low in sintering process window, good in acid and alkali resistance, welding performance, wear resistance and ink matching performance and the like by adopting a silver powder system of a polycrystalline-gap structure, low-melting-point glass powder and various special functional auxiliaries, and the technical requirements of'pressing method 'process production can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of automobile glass heating, and relates to a glass composition, inorganic glass powder and a preparation method thereof, and an automobile pressed glass conductive silver paste and a preparation method thereof. Background Art

[0002] With the continuous development and growth of my country's automobile industry and technological upgrading, the manufacturing process of automotive glass has gradually upgraded from traditional hot bending self-weight molding and tempered molding to fully automatic glass shaping production, that is, the new "pressing method" process, which can be divided into single-piece pressing process and double-piece pressing process. Compared with the molding temperature of 650-720℃ in the traditional process, the molding temperature of the pressing furnace is greatly reduced (the maximum temperature is 650℃), the production efficiency is greatly improved (generally 3min), and the comprehensive energy consumption is significantly reduced. In view of the fact that the new "pressing method" process integrates temperature, flexibility and strength, the deviation rate of the glass processed by extrusion molding can be controlled between ±1mm, and the streamlined sense and clarity of the appearance have more performance advantages, and the prospects are broad.

[0004] As conductive silver paste for traditional molding process of automobile glass, various conductive silver pastes have been developed. For example, Chinese patent CN101613186A discloses lead-free silver paste for high-temperature sintering automobile glass heating wire and its preparation method, Chinese patent CN 113539545A discloses a gray conductive silver paste for automobile glass and its preparation method, Chinese patent CN114171238A discloses a low-resistance silver paste for automobile glass and its preparation method, and Chinese patent CN 105761777A discloses a fine line silver paste for automobile glass and its preparation method.

[0005] However, these conductive silver pastes cannot meet the requirements of the pressing process. Summary of the invention

[0006] The purpose of the present invention is to provide a glass composition, an inorganic glass powder and a preparation method thereof, and an automotive pressed glass conductive silver paste and a preparation method thereof. The present invention, together with a silver powder system using a polycrystalline-gap structure, a low-melting-point glass powder and various special functional additives, has the advantages of a low sintering process window, acid and alkali resistance, welding performance, wear resistance, good ink matching, etc., and can meet the technical requirements of the "pressing method" process production.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A first aspect of the present invention provides a glass composition, comprising a first glass composition and a second glass composition in a mass ratio of (10-90):(30-70);

[0009] The first glass composition includes the following components and their contents by weight:

[0010]

[0011] The second glass composition includes the following components and their contents by weight:

[0012]

[0013] The second aspect of the present invention provides a method for preparing an inorganic glass powder based on the above-mentioned glass composition, comprising: heating and melting the first glass composition and the second glass composition respectively, quenching with water to obtain first glass beads and second glass beads, ball-milling them into powder, and mixing them to obtain inorganic glass powder.

[0014] Furthermore, in the heating and melting, the heating temperature is 1100-1300° C., preferably 1150-1250° C., and the heating time is preferably 30-60 min; and / or,

[0015] In the ball milling, the ball milling medium is ethanol, the ball milling balls are made of zirconium oxide, the mass ratio of the ball milling balls, the solid phase obtained by water quenching, and the ball milling medium is 2.2:1:0.3, the ball milling speed is 150-250rpm, and the ball milling time is 24-48h.

[0016] The third aspect of the present invention provides a conductive silver paste for automotive pressed glass, comprising the following components and their weight percentages:

[0017]

[0018] Furthermore, the functional additive is selected from at least one of nickel oxide, titanium dioxide, manganese dioxide, molybdenum trioxide, bismuth trioxide, iron trioxide, cobalt tetroxide, cobalt phosphate or vanadium pentoxide.

[0019] Furthermore, the true density of the spherical silver powder is 5.30-6.25 g / cm 3 , bulk density is 3.0-4.0g / cm 3 , the average particle size is 1.0-2.0μm, and the specific surface area is 0.35-0.75m 2 / g.

[0020] The fourth aspect of the present invention provides a method for preparing an automotive pressed glass conductive silver paste, comprising: mixing an organic carrier with an inorganic glass powder, adding a functional additive and mixing, then adding spherical silver powder and mixing, grinding, and obtaining an automotive pressed glass conductive silver paste.

[0021] Furthermore, the method for preparing the organic carrier includes: dissolving a polymer resin in an organic solvent, adding a dispersant and mixing, to obtain the organic carrier.

[0022] Furthermore, the polymer resin is selected from at least one of acrylic resin, ethyl cellulose, nitrocellulose, ethyl hydroxyethyl cellulose or wood rosin; the organic solvent is selected from at least one of terpineol, turpentine, diethylene glycol butyl ether, diethylene glycol dibutyl ether, butyl carbitol acetate, dipropylene glycol monomethyl ether or tripropylene glycol monomethyl ether; the dispersant is selected from at least one of ED120, ED420 or KD16.

[0023] Furthermore, the grinding includes 5-7 times of intermittent progressive grinding and dispersion through a three-roller grinder, and the grinding fineness of the obtained slurry is less than 12 μm and the viscosity is 20-30 Pa·S.

[0024] Compared with the prior art, the present invention has the following characteristics:

[0025] The two groups of glass powders provided by the present invention are mixed with metal silver powder, organic carrier and special functional additives and slurried to meet the sintering window of the automobile glass pressing process.

[0026] The present invention uses highly active silver powder with a structure of polycrystalline and loose gaps, which not only plays a conductive role but also significantly optimizes the sintering window of the conductive paste.

[0027] The special functional additives selected in the present invention not only play the basic properties such as wetting and dispersion, but also greatly improve the acid and alkali resistance of the conductive paste. The automotive pressed glass conductive silver paste of the present invention also has excellent wear resistance, welding performance and ink matching, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a field emission scanning electron microscope image of the automotive pressed glass sample prepared in Example 1. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] A glass composition comprising a first glass composition and a second glass composition in a mass ratio of (10-90):(30-70);

[0031] The first glass composition includes the following components and their contents by weight:

[0032]

[0033] The second glass composition includes the following components and their contents by weight:

[0034]

[0035] The glass composition is mixed with conductive metal silver powder, organic carrier and special functional additives and slurried to obtain a conductive silver paste with high welding strength, excellent acid and alkali resistance, outstanding wear resistance and good black glaze matching. During the pressing process of the conductive silver paste containing the glass composition, the second glass composition will melt and flow toward the glass substrate surface in the early stage, bringing the metal silver powder particles to the glass substrate surface, and exerting excellent bonding properties; in the later stage, as the temperature further increases, the first glass composition begins to soften and penetrates the structure of the conductive silver paste in the form of a skeleton, which enhances the hardness and wear resistance of the silver paste.

[0036] In the glass composition, the glass formed by Bi2O3, SiO2, B2O3, ZnO, Na2O, Al2O3, K2O and CaO is Bi2O3-B2O3-SiO2, Bi2O3-B2O3-SiO2-ZnO system; B2O3 and SiO2 are the network-shaped body of the glass, constituting the basic skeleton structure; Bi2O3 is the network destroyer of the glass, constituting the node of the silicon-oxygen skeleton break; ZnO and Al2O3 are the intermediate oxides of the glass, which can participate in the formation of the network and also act as regulators.

[0037] In the glass composition, Sb2O3 acts as a clarifier during the glass melting process to eliminate bubbles. In addition, the addition of Sb2O3 can increase the hardness and wear resistance of the glass powder, which helps to improve the overall wear resistance of the conductive silver paste.

[0038] In the glass composition, SiO2 helps to improve the acid resistance and stability of the glass powder. The acid resistance of glass composition B# is the best, and the overall acid resistance of the conductive silver paste is simultaneously improved.

[0039] In the glass composition, Na2O and K2O are helpful to improve the fluidity of the glass powder when it softens, and optimize the welding performance between the conductive silver paste and the automobile glass.

[0040] In the glass composition, the mixing ratio of the first glass composition to the second glass composition is 10:90 to 30:70 by weight, and more preferably 15:85 to 25:75 by weight.

[0041] The glass composition provided by the present invention is in powder form, and D50 is less than 3 μm, which is beneficial to the subsequent preparation of conductive silver paste.

[0042] The glass composition provided by the present invention is amorphous, that is, the crystallinity is 0%.

[0043] A method for preparing inorganic glass powder based on the above glass composition comprises: heat-insulating and completely melting the first glass composition and the second glass composition respectively, quenching with water, filtering to obtain first glass beads and second glass beads, and finally ball-milling the first glass beads and the second glass beads respectively, and mixing to obtain inorganic glass powder.

[0044] In some specific embodiments, the first glass composition and the second glass composition are mixed by a V-type mixer for 1-3 hours, and preferably, the mixture is sieved through 100 mesh.

[0045] In some specific embodiments, during the melting, the melting temperature is 1100-1300° C., preferably 1150-1250° C., and the heating time is preferably 30-60 min.

[0046] In some specific embodiments, in the ball milling, the ball milling medium is ethanol, the ball milling balls are made of zirconia, the mass ratio of the ball milling balls, the solid phase obtained by water quenching, and the ball milling medium is 2.2:1:0.3, the ball milling speed is 150-250rpm, and the ball milling time is 24-48h.

[0047] In some specific embodiments, the particle size D50 of the inorganic glass powder is 2-3 μm, the melting temperature of the first inorganic glass powder is 600-700°C, and the melting temperature of the second inorganic glass powder is 550-650°C.

[0048] A conductive silver paste for automobile pressed glass, comprising the following components and their weight percentages:

[0049]

[0050] In some specific embodiments, the automotive pressed glass conductive silver paste includes the following components and their weight percentages:

[0051]

[0052] In some specific embodiments, the functional additives include flux, colorant or corrosion resistance, mainly selected from inorganic oxides, such as at least one of nickel oxide, titanium dioxide, manganese dioxide, molybdenum trioxide, bismuth trioxide, iron trioxide, cobalt tetroxide, cobalt phosphate or vanadium pentoxide.

[0053] In some specific embodiments, the spherical silver powder is a polycrystalline, loose interstitial structure and high-activity silver powder, and the true density is 5.30-6.25 g / cm 3 , bulk density is 3.0-4.0g / cm 3 , the average particle size is 1.0-2.0μm, and the specific surface area is 0.35-0.75m 2 / g.

[0054] A method for preparing conductive silver paste for automobile pressed glass comprises: mixing an organic carrier with inorganic glass powder, adding a functional additive and mixing, then adding spherical silver powder and mixing, grinding, and obtaining the conductive silver paste for automobile pressed glass.

[0055] In some specific embodiments, the method for preparing the organic carrier includes: dissolving a polymer resin in an organic solvent, adding a dispersant and mixing, to obtain an organic carrier.

[0056] In some specific embodiments, the polymer resin is selected from at least one of acrylic resin, ethyl cellulose, nitrocellulose, ethyl hydroxyethyl cellulose or wood rosin.

[0057] In some specific embodiments, the organic solvent is selected from at least one of terpineol, turpentine, diethylene glycol butyl ether, diethylene glycol dibutyl ether, butyl carbitol acetate, dipropylene glycol monomethyl ether or tripropylene glycol monomethyl ether. Preferably, the organic solvent is diethylene glycol butyl ether.

[0058] In some specific embodiments, the dispersant is selected from at least one of ED120 dispersant, ED420 dispersant of Kusumoto Chemicals Co., Ltd. or KD16 dispersant of Croda Chemicals (Shanghai) Co., Ltd., preferably a copolymer of carboxylic acid groups.

[0059] In some specific embodiments, in the mixture of polymer resin, organic solvent and dispersant, the mass fraction of polymer resin is 5-30%, preferably 12-25%, the mass fraction of auxiliary agent is preferably 1-3%, and the rest is solvent, which has excellent coating performance.

[0060] In some specific embodiments, the grinding includes 5-7 times of intermittent progressive grinding and dispersion through a three-roller grinder, and the grinding fineness of the obtained slurry is less than 12 μm and the viscosity is 20-30 Pa·S.

[0061] In some specific embodiments, spherical silver powder, inorganic glass powder and functional additives are directly added to the organic carrier and quickly dispersed by a high-speed disperser for 30 minutes to ensure that various components in the slurry are evenly dispersed.

[0062] The conductive silver paste for automobile pressed glass of the present invention not only meets the basic sintering and molding process of automobile pressed glass, but also has excellent wear resistance, welding performance, ink matching and the like.

[0063] This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0064] The following are more detailed implementation cases, which further illustrate the technical solutions of the present invention and the technical effects that can be obtained.

[0065] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.

[0066] Example 1

[0067] A conductive silver paste SP1 for automobile pressed glass, the preparation method of which comprises the following steps:

[0068] (1) Preparation of inorganic glass powder:

[0069] Glass composition B#: 61 parts by weight of Bi2O3, 27 parts by weight of SiO2, 5 parts by weight of B2O3, 3 parts by weight of Sb2O3, 1.5 parts by weight of Na2O, 0.3 parts by weight of Al2O3, 0.3 parts by weight of K2O, 0.5 parts by weight of Li2O, and 0.3 parts by weight of CaO;

[0070] Glass composition C#: 66 parts by weight of Bi2O3, 22 parts by weight of B2O3, 3 parts by weight of ZnO, 4 parts by weight of SiO2, 2 parts by weight of CaF2, 1.5 parts by weight of Al2O3, 1 part by weight of MgO, and 0.3 parts by weight of Sb2O3;

[0071] The two compositions were stirred evenly by a V-type mixer, transferred into a corundum crucible, and placed into a silicon-molybdenum rod resistance furnace. When the temperature was raised to 1200°C, the mixture was kept warm for 30 minutes, and then quenched with water and filtered to obtain glass beads.

[0072] Glass beads were placed in a ball milling jar at a mass ratio of zirconium oxide balls: glass beads: ethanol = 2.2:1:0.3, the jar was rotated at 200 rpm, and after 24 hours of ball milling, the particle size distribution was tested. The glass powder of composition B# was mixed with the glass powder of composition C# at a mixing mass ratio of 20:80 to obtain the inorganic glass powder G1 of this embodiment.

[0073] (2) Preparation of organic carrier:

[0074] Weigh 88 parts by weight of diethylene glycol butyl ether, add 12 parts by weight of ethyl cellulose STD-7 (Dow viscosity is 7) produced by Dow Chemical (China) Co., Ltd., raise the temperature to 80°C and keep the temperature constant. After the ethyl cellulose resin is completely dissolved, filter on a 400-mesh cloth to remove impurities. Finally, add 5 parts by weight of dispersant ED420 at room temperature, stir evenly to obtain the organic carrier V12.

[0075] (3) Preparation of conductive silver paste:

[0076] 10 parts by weight of organic carrier V12 was weighed and placed in a stainless steel barrel, and 4 parts by weight of inorganic glass powder G-1 was added under stirring, and stirred evenly. Then, 0.5 parts by weight of cobalt phosphate and 0.5 parts by weight of vanadium pentoxide were added and stirred evenly.

[0077] Finally, 85 parts by weight of the metal silver powder QH-1 of Hubei Ha Shen Green Energy New Materials Co., Ltd. was added in batches and stirred at high speed. The mixture was ground seven times using a three-roll mill with a diameter of 260 mm. The grinding slurry had a fineness of 11 μm and a viscosity of 25 Pa·S, and the automotive pressed glass conductive silver paste SP1 was obtained.

[0078] Example 2

[0079] A conductive silver paste SP2 for automobile pressed glass, the preparation method of which is different from that of Example 1 in that:

[0080] In step (1), glass composition B#: 65 parts by weight of Bi2O3, 24 parts by weight of SiO2, 5 parts by weight of B2O3, 3 parts by weight of Sb2O3, 1.5 parts by weight of Na2O, 0.3 parts by weight of Al2O3, 0.3 parts by weight of K2O, 0.5 parts by weight of Li2O, and 0.3 parts by weight of CaO;

[0081] Glass composition C#: 68 parts by weight of Bi2O3, 20 parts by weight of B2O3, 3 parts by weight of ZnO, 3 parts by weight of SiO2, 2 parts by weight of CaF2, 1.5 parts by weight of Al2O3, 1 part by weight of MgO, and 0.3 parts by weight of Sb2O3;

[0082] The obtained inorganic glass powder was recorded as G2.

[0083] The rest is the same as in Example 1.

[0084] Example 3

[0085] A conductive silver paste SP3 for pressed glass for automobiles, the preparation method of which is different from that of Example 1 in that:

[0086] In step (1), glass composition B#: 59 parts by weight of Bi2O3, 28 parts by weight of SiO2, 5 parts by weight of B2O3, 2 parts by weight of Sb2O3, 1.5 parts by weight of Na2O, 0.3 parts by weight of Al2O3, 0.3 parts by weight of K2O, 0.5 parts by weight of Li2O, and 0.3 parts by weight of CaO;

[0087] Glass composition C#: 64 parts by weight of Bi2O3, 24 parts by weight of B2O3, 3 parts by weight of ZnO, 3 parts by weight of SiO2, 2 parts by weight of CaF2, 1.5 parts by weight of Al2O3, 1 part by weight of MgO, and 0.3 parts by weight of Sb2O3;

[0088] The obtained inorganic glass powder was recorded as G3.

[0089] The rest is the same as in Example 1.

[0090] Example 4

[0091] A conductive silver paste SP4 for automobile pressed glass, the preparation method of which is different from that of Example 1 only in that:

[0092] In step (3), 14 parts by weight of organic carrier V12 was weighed and placed in a stainless steel barrel, and 5 parts by weight of inorganic glass powder G-1 was added under stirring and stirred evenly. Then, 0.5 parts by weight of bismuth trioxide and 0.5 parts by weight of vanadium pentoxide were added and stirred evenly.

[0093] Finally, 80 parts by weight of metal silver powder QH-1 were added in batches and stirred at high speed. The mixture was ground seven times using a three-roll mill with a diameter of 260 mm. The grinding slurry had a fineness of 10 μm and a viscosity of 28 Pa·S, and the automotive pressed glass conductive silver paste SP4 was obtained.

[0094] Example 5

[0095] A conductive silver paste SP5 for automobile pressed glass, the preparation method of which is different from that of Example 1 only in that:

[0096] In step (3), 18 parts by weight of organic carrier V12 was weighed and placed in a stainless steel barrel, and 6 parts by weight of inorganic glass powder G-1 was added under stirring and stirred evenly. Then, 0.5 parts by weight of bismuth trioxide and 0.5 parts by weight of vanadium pentoxide were added and stirred evenly.

[0097] Finally, 75 parts by weight of metal silver powder QH-1 were added in batches and stirred at high speed. The mixture was ground six times using a three-roll mill with a diameter of 260 mm. The grinding slurry had a fineness of 10 μm and a viscosity of 27 Pa·S, and the automotive pressed glass conductive silver paste SP5 was obtained.

[0098] Comparative Example 1

[0099] A conductive silver paste D1 for automobile pressed glass, the preparation method of which is different from that of Example 1 in that, in the ball milling of step (1), only the glass powder of composition B# is used while the total amount of glass powder remains unchanged, and the rest is the same as that of Example 1.

[0100] Comparative Example 2

[0101] A conductive silver paste D2 for automobile pressed glass, the preparation method of which is different from that of Example 1 in that, in the ball milling of step (1), only the glass beads of composition C# are used while the total amount of glass powder remains unchanged, and the rest is the same as that of Example 1.

[0102] Application examples:

[0103] This example is used to characterize the performance of the automotive pressed glass conductive silver paste prepared in Examples 1 to 5, including:

[0104] 1. Performance test of inorganic glass powder:

[0105] The particle size distribution and melting temperature of the inorganic glass powder G1-G3 were tested using a laser particle size analyzer (Jinan Micro-Nano Particle Technology Co., Ltd.), see Table 1.

[0106] Table 1

[0107]

[0108] 2Performance test of conductive silver paste for automotive pressed glass:

[0109] Examples 1-5 were screen printed on automobile glass (note: black glaze overprinted glass) using a 200-mesh screen. The original glass sheet had a thickness of 4 mm, a length and width of 2 m*1 m, and printed silver paste circuits (including busbars arranged in parallel at both ends and lines vertically connected between the busbars, the width of the line was 0.5 mm, the length of the line was 1200 mm, the number of lines was 10, the width of the busbar was 10 mm, and the length of the busbar was 650 mm). Then, it entered a tunnel furnace, the drying temperature was 150°C, the drying time was 20 min, and finally it entered a pressing furnace, the pressing temperature was 620-650°C, the time was 3 min, and it was cooled and formed to obtain automobile pressed glass samples.

[0110] (1) Silver content: GB / T 10046-2008;

[0111] (2) Resistance performance: Use a multimeter to directly test the resistance between the two ends of the busbar in the silver paste circuit;

[0112] (3) Welding strength: Lead-free solder is used at the busbars at both ends of the glass at a temperature of 350°C, and the test is performed using a tensile test machine after cooling;

[0113] (4) Acid resistance: After annealing, the sample was cut into pieces with a size of 100 mm*100 mm and directly immersed in a 0.1 N sulfuric acid solution at 80°C for 4 hours. After drying, the Scotch 2525 tape was applied and the peeling and shedding of the silver wire was observed.

[0114] (5) Wear resistance: The wear tester TABER 5135, rotor CS-10F, load 100 g, rotation number 1000 rpm were used to test the change rate of the silver wire resistance before and after wear resistance.

[0115] The above test results are shown in Table 2.

[0116] Table 2

[0117] SP1 SP2 SP3 SP4 SP5 Silver content 84.60% 84.70% 84.50% 79.80% 74.70% Solid content 89.60% 89.70% 89.50% 85.80% 80.70% Electrical properties 0.85Ω 0.84Ω 0.87Ω 0.97Ω 1.05Ω Welding strength 256N 263N 268N 254N 249N Acid resistance 4 hours 4 hours 5 hours 4 hours 4 hours Wear resistance ΔR=3.8% ΔR=4.2% ΔR=4.1% ΔR=5.1% ΔR=5.4% Black glaze matching excellent excellent excellent excellent excellent

[0118] 3Microscopic test of conductive silver paste for automotive pressed glass:

[0119] The microscopic morphology of the formed (SP1) automotive pressed glass sample was analyzed using a field emission scanning electron microscope (SEM). Figure 1 The results show that the interface between the metallic silver powder particles, molten glass powder and special functional additives is very dense.

[0120] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A glass composition, characterized in that: A first glass composition and a second glass composition in a mass ratio of (10-90):(30-70); The first glass composition includes the following components and their contents by weight: The second glass composition includes the following components and their contents by weight:

2. A method for preparing an inorganic glass powder based on the glass composition according to claim 1, characterized in that: The method comprises: heating and melting the first glass composition and the second glass composition respectively, quenching with water to obtain first glass beads and second glass beads, ball-milling to powder, and mixing to obtain inorganic glass powder.

3. The method for preparing inorganic glass powder according to claim 2, characterized in that: In the heating and melting, the heating temperature is 1100-1300° C.; and / or, In the ball milling, the ball milling medium is ethanol, the ball milling balls are made of zirconium oxide, the mass ratio of the ball milling balls, the solid phase obtained by water quenching, and the ball milling medium is 2.2:1:0.3, the ball milling speed is 150-250rpm, and the ball milling time is 24-48h.

4. A conductive silver paste for pressed glass of automobile, characterized in that: Includes the following components and weight percentage: The inorganic glass powder is prepared by the method as claimed in claim 2 or 3.

5. The conductive silver paste for pressed glass for automobile according to claim 4, characterized in that: The functional additive is selected from at least one of nickel oxide, titanium dioxide, manganese dioxide, molybdenum trioxide, bismuth trioxide, iron trioxide, cobalt tetroxide, cobalt phosphate or vanadium pentoxide.

6. The conductive silver paste for pressed glass for automobile according to claim 4, characterized in that: The true density of the spherical silver powder is 5.30-6.25 g / cm 3 , bulk density is 3.0-4.0g / cm 3 , the average particle size is 1.0-2.0μm, and the specific surface area is 0.35-0.75m 2 / g.

7. A method for preparing the conductive silver paste for automobile pressed glass according to any one of claims 4 to 6, characterized in that: include: The organic carrier is mixed with the inorganic glass powder, and then a functional additive is added and mixed, and then spherical silver powder is added and mixed, and ground to obtain the automotive pressed glass conductive silver paste.

8. The method for preparing the conductive silver paste for automobile pressed glass according to claim 7, characterized in that: The method for preparing the organic carrier comprises: dissolving a polymer resin in an organic solvent, adding a dispersant and mixing to obtain the organic carrier.

9. The method for preparing the conductive silver paste for automobile pressed glass according to claim 8, characterized in that: The polymer resin is selected from at least one of acrylic resin, ethyl cellulose, nitrocellulose, ethyl hydroxyethyl cellulose or wood rosin; the organic solvent is selected from at least one of terpineol, turpentine, diethylene glycol butyl ether, diethylene glycol dibutyl ether, butyl carbitol acetate, dipropylene glycol monomethyl ether or tripropylene glycol monomethyl ether; the dispersant is selected from at least one of ED120, ED420 or KD16.

10. The method for preparing the conductive silver paste for automobile pressed glass according to claim 7, characterized in that: The grinding includes 5-7 times of intermittent progressive grinding and dispersion through a three-roller grinder, and the grinding fineness of the obtained slurry is less than 12 μm and the viscosity is 20-30 Pa·S.

Citation Information

Patent Citations

  • Lead-free silver slurry for high-temperature sintered automobile glass heating wire and preparation method thereof

    CN101613186A

  • Filament silver paste for automobile glass and preparation method of filament silver paste

    CN105761777A

  • Grey conductive silver paste for automobile glass and preparation method thereof

    CN113539545A

  • Low-resistance silver paste for automobile glass and preparation method of low-resistance silver paste

    CN114171238A

Cited By

  • High-nickel-content conductive paste for N-type Topcon photovoltaic cell and preparation method of high-nickel-content conductive paste

    CN121171686A

  • A high nickel content conductive paste for N-type topcon photovoltaic cells and a method of making the same

    CN121171686B

  • Special glass powder for conductive silver paste for demisting line of rear window of automobile as well as preparation method and application of special glass powder

    CN122079499A

  • Glass composition, inorganic glass powder and preparation method therefor, and conductive silver paste for automotive pressed glass and preparation method therefor

    WO2026143942A1